A Numerical Analysis of the Leakage Characteristics of an Embankment Dam Slope With Internal Erosion - Jia, Yu; Ding, Yu; Wang, Xuan; Zhang, Jiasheng; Chen, Xiaobin (Frontiers in Earth Science, 2022)
Leakage is a common defect of embankment dam slopes and is usually accompanied by internal erosion. This paper establishes a mathematical two-phase seepage coupling model that explicitly considers the effects of internal erosion. With the help of the finite element software COMSOL Multiphysics®, we use this model model to study the characteristics of fluid seepage, the fraction of leakage volume that is made up of migrated fine particles (migrated fine particles volume fraction), porosity, permeability, and displacement in the leakage process of a three-dimensional embankment dam slope, as well as to study the influence of the water level and leakage outlet size on the above features. Our results show that water seepage velocity gradually increases with the time, especially at the downstream leakage outlet. Therefore, the erosion and migration of fine particles occur primarily at the downstream leakage outlet, resulting in a significant increase in the migrated fine particles volume fraction, porosity, and permeability. In addition, the maximum migrated fine particles volume fraction, the maximum porosity, and the maximum permeability in the slope increase nonlinearly with time. Curves for maximum displacement with a strength reduction factor can be divided into three stages: the early stable stage, the midterm nonlinear growth stage (creeping state), and the later rapid growth stage (instability state). We also find that the rise of the water level promoted the erosion and migration of fine particles on the slope and that the maximum migrated fine particles volume fraction and the maximum porosity increased with water level. The values of the strength reduction factor for the creeping state and the slope does not decrease as the water level rises. Furthermore, the larger the size of the downstream leakage outlet, the larger the maximum migrated fine particles volume fraction and maximum porosity. However, the relationship between maximum displacement and strength reduction factor was nearly unaffected by the size of the leakage outlet.